Pemanfaatan Data Education Management Information System (EMIS) Untuk Meningkatkan Mutu Pelayanan Sekolah di MTsN 3 Kota Pariaman - Mirna Sri Holanda (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
This research is motivated by the use of EMIS applications that have not been realized optimally because there are still obstacles faced. The purpose of this study was to determine the Education Management Information System (EMIS) in improving the quality of school services: the EMIS Application Program, the use of the EMIS Application in improving the quality of services at MTsN 3 Pariaman City, and to determine the supporting and inhibiting factors for the use of the EMIS application. This research uses descriptive qualitative method. Data obtained through interviews, observation and documentation. Data analysis techniques in this study are data reduction, data presentation and conclusion drawing/verification. The research findings are: (1) The EMIS program consists of a dashboard that includes school profile data, student data, teacher data, and education staff as a whole, and infrastructure data includes data on existing infrastructure in schools; (2) The use of the EMIS application starts from opening google chrome or mozilla firefox, then typing the link provided, logging in using the username and password. After entering the main menu, the operator can choose which menus to click to fill in the EMIS data. (3) The supporting factor for the use of EMIS is the role of the school principal in providing the necessary facilities and infrastructure including hardware consisting of a laptop or computer, and software including hotspots or WIFI networks, then directing school operators to follow existing zoom or training in order to increase knowledge and skills of the operator. The inhibiting factor in using EMIS is sometimes a system error, the latest EMIS must upload files from old student data.